Potential Solar Power Sources at the Indonesian Border Post Papua New Guinea - Haloho, Luwis Surani; Martha, Sukendra; Supriyadi, Asep Adang; Sadewa, Annisa Harum (Formosa Journal of Multidisciplinary Research, 2024)
The border post serves as a means of supervision, security, and community services in the border area between Indonesia and Papua New Guinea. Electricity needs have not been met due to limitations both in terms of economic and geographical conditions. To overcome this problem, the method is measure the potential of solar power sources in the area using GIS data from NASA Prediction of Worldwide Energy Resources (POWER) which provides data on solar radiation and temperature in a 5-year period (2018-2022). So that the potential for solar electricity is obtained, which is 4.974 kWh/m2 /day, which means that it has the potential for the construction of solar power plants.